The Design of Media on Two-Lens System Experiment (MTLSE) for Pre-service Physics Teachers - Saprudin, Saprudin; Liliasari, Liliasari; Prihatmanto, Ary Setijadi; Setiawan, Andhy (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2018)
This article is a part of the research in designing a model of the geometrical-optics game on optics’ courses for pre-service physics teachers (PPTs). This article describes the preliminary form of product, the result of validation, and PPTsâ€™ responses to the media on two-lens system experiment (MTLSE). The validation of this media has been done according to physics subject matter, instructional media and pedagogical experts. The implementation of MTLSE using the one-shot case study design involving 25 PPTs at one of the Islamic universities in Bandung. We collected the data of MTLSE validation and PPTsâ€™ responses through non-test techniques with questionnaire instruments. The data using quantitative descriptive analysis technique. The results of MTLSE validation can be good categorized. Besides, generally, the PPTsâ€™ responses are good categorized toward the implementation of MTLSE on optics’ courses.